Early and Late Complications Associated with Penile Cancer Surgery and the Impact of Human Papillomavirus Status: Findings from a Retrospective Norwegian Cohort Study - Patrick Juliebø-Jones; Ida M. Nordanger; Christian Beisland; Tor K. Thorkelsen; Alfred Honoré; Christian A. Moen (European Urology Open Science)
Background and objective: Penile cancer (PeCa) and penile intraepithelial neoplasia (PeIN) are rare diseases, and the burden of complications associated with surgery remains under-reported. The objective was to evaluate the early (≤30 d) and late (>30 d) complications and the impact of human papillomavirus (HPV) status. Methods: A retrospective analysis was conducted of a cohort consisting of 201 consecutive and treatment-naïve patients with PeCa/PeIN undergoing surgery (penile sparing, and partial and total amputation) between January 1, 2000 and December 31, 2023 at a tertiary centre as part of a centralised regional service. Key findings and limitations: The median follow-up time was 39 (interquartile range 21, 76) mo. The early and late patient complication rates were 45% and 38%, respectively. Of the patients, 18.5% experienced two or more early complications. A majority (80%) of early complications were minor (Clavien-Dindo ≤2). There was a 1% admission rate to the intensive care unit, but no deaths were recorded within 30 d. Body mass index (BMI)was a significant predictor of early complications (p = 0.01). Late complications included chronic wound irritation (10%) and urethral stricture (11%). The latter was highest among those who had undergone partial amputation. One in four patients underwent reoperation due to recurrence during follow-up. HPV status had no association with the rate of either early or late complications. Conclusions and clinical implications: PeCa surgery is associated with a relatively high complication burden, in both the early and the late postoperative period. Lymph node surgery further adds to the morbidity profile. BMI was a significant predictor of having an early complication, while HPV status did not affect the rate of early or late complications. Patient summary: Penile cancer surgery is associated with a high rate of complications in early as well as late postoperative period. However, most of these complications are not severe. Body mass index was a significant predictor of an early complication, but human papillomavirus status was not associated with the risk of complications.